LGBT Activism and the Making of Europe : A Rainbow Europe? - Ayoub, Phillip M.; Paternotte, David; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
This book explores the alleged uniqueness of the European experience, and investigates its ties to a long history of LGBT and queer movements in the region. These movements, the book argues, were inspired by specific ideas about Europe, which they sought to realize on the ground through activism.
Keywords: Social sciences; Political science; Political communication; Europe -- Politics and government; Social policy; Public administration; Sociology; Sex (Psychology).; Gender expression; Gender identity; Social Sciences; Social Policy; Gender Studies; Political Science; European Politics; Public Administration; Political Communication